WD J004917.14−252556.81: the most massive pulsating white dwarf - Kilic, Mukremin (2023)
We present Apache Point Observatory (APO) and Gemini time-series photometry of WD J004917.14−252556.81, an ultramassive DA white dwarf with Teff = 13 020 K and log g = 9.34. We detect variability at two significant frequencies, making J0049−2525 the most massive pulsating white dwarf currently known with M★ = 1.31 M☉ (for a CO core) or 1.26 M☉ (for an ONe core). J0049−2525 does not display any of the signatures of binary mergers, there is no evidence of magnetism, large tangential velocity, or rapid rotation. Hence, it likely formed through single star evolution and is likely to have an ONe core. Evolutionary models indicate that its interior is ≳99 per cent crystallized. Asteroseismology offers an unprecedented opportunity to probe its interior structure. However, the relatively few pulsation modes detected limit our ability to obtain robust seismic solutions. Instead, we provide several representative solutions that could explain the observed properties of this star. Extensive follow-up time-series photometry of this unique target has the potential to discover a significant number of additional pulsation modes that would help overcome the degeneracies in the asteroseismic fits, and enable us to probe the interior of an ≈1.3 M☉ crystallized white dwarf.